(untitled) (gjstudies, 2014)
This research introduces a novel, hybrid methodological framework for predicting corporate financial distress by integrating conventional accounting ratios with a unique, multidimensional characterization of firm-specific attributes, including governance structures,strategic flexibility, and intangible asset profiles. Departing from traditional bankruptcyprediction models that predominantly rely on financial statement data, this study proposesa ’Firm Resilience Quotient’ (FRQ), a composite metric derived from both quantitativefinancial indicators and qualitative, ordinal assessments of managerial adaptability and operational robustness. The methodology employs a two-stage analytical process: first, a modified discriminant analysis identifies firms exhibiting early-stage financial vulnerability froma set of twenty-two accounting ratios; second, a bespoke ordinal logistic regression model,incorporating the FRQ and other firm characteristics, predicts the probability and timing ofdistress over a three-year horizon. The model is trained and validated on a unique longitudinal dataset of 1,450 U.S. manufacturing and service firms from 1995 to 2004, deliberatelyexcluding the dot-com bubble peak and trough to focus on structural rather than cyclicalfailure. Results demonstrate a significant improvement in predictive accuracy, achieving aType I error rate of 8.7% and a Type II error rate of 12.3% in out-of-sample testing, outperforming established models like Altman’s Z-score and the Ohlson O-score by 14% and11%, respectively. More importantly, the findings reveal that non-financial characteristicsrelated to governance decentralization and RD intensity are more significant leading indicators of distress than liquidity ratios in technology-intensive sectors, challenging conventionalwisdom. This work contributes a more holistic, forward-looking tool for stakeholders andestablishes that the pathway to distress is increasingly mediated by strategic and organizational factors inadequately captured by financial ratios alone